Measuring the Impact of Lean Techniques on Performance Indicators in Logistics Operations - Dehdari, Payam (Wissenschaftliche Berichte des Institutes für Fördertechnik und Logistiksysteme des Karlsruher Instituts für Technologie, 2013)
Several in-depth studies have verified the positive impact of lean techniques on performance indicators in production environments. Studies performed on warehouse environments have partially confirmed this. This thesis helped to close the gap between the disparities in the level of evidence mentioned above. A study was conducted that included 16 warehouses in an observation group and 56 warehouses in a control group. These significant results help close the gap in the evidence.